The Role of Constitutional Law in Realizing Modern Government in the Digital Era - Evelyn, Silvia; Athayya, Keira Adzra (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
This study aims to determine and analyze the role of Constitutional Law to realize a modern government system and understand the digital system in a global era that is increasingly developing from year to year. The method used to conduct this research is normative juridical research. Normative research is research whose data collection process is through logical, systematic and based on applicable law. Constitutional Law is a set of legal regulations governing the order of state structures, mechanisms of relationships between organ structures or state structures, and mechanisms of relationships between state structures, as well as mechanisms between state structures and citizens. Along with the rapid development of technology that has an impact on constitutional law, it is necessary to adapt and develop a legal framework that is in accordance with the digital era.